Performance analyses of desiccant wheel-assisted atmospheric water harvesting system using renewable heating and cooling sources. (15th January 2022) - Liu, Mengdan; Tu, Rang; Wu, Zilei; Zhu, Jie
Highlights: Study a novel water harvesting system using renewable heat/cold sources. Solar thermal energy and ambient air are used as the heat and cold sources. Summarize effective air handling processes with desiccant wheels for humid regions. Give operation strategies for practical applications under annual weather conditions. Abstract: This paper proposes an atmospheric water harvesting system that can be operated using renewable heating and cooling sources. It is intended for use in humid regions. The system uses multistage desiccant wheels to increase the humidity ratio of the processed air before it is condensed to collect water. Theoretical analyses of the cascade humidification cycles were performed, and parametric analyses were performed to identify the optimal system configurations, e.g., the wheel structure, total wheel thickness, and stage number. The results can be used to maximize water harvesting rate ( WHR ) under different weather conditions and different heating/cooling-source temperatures. Under annual weather conditions of four typical cities in South China, the area ratio of the wheel is recommended to be 1. Considering both the total thickness of the wheels and the stage number, the recommended wheel thickness in each stage is 100 mm. Increasing the stage number led to a high WHR . However, the water harvesting efficiency first increased and then decreased. The optimal stage number with the maximum water-harvesting efficiency depends on the weather conditions. The optimal number of parallel humidification systems was studied for a total wheel thickness of 1200 mm and a stage number of 12. Under weather conditions of 28 °C and 20 g/kg, the maximum WHR is 95.2 kg/h, which is realized when the number of parallel humidifying systems is 3. Considering the heating and cooling temperatures and heat-transfer efficiencies, the numbers of parallel humidifying systems needed to achieve the maximum WHR under different weather conditions were identified.